2009
DOI: 10.1667/rr1688.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Cataractogenesis: A Review of Recent Studies

Abstract: The lens of the eye is recognized as one of the most radiosensitive tissues in the human body, and it is known that cataracts can be induced by acute doses of less than 2 Gy of low-LET ionizing radiation and less than 5 Gy of protracted radiation. Although much work has been carried out in this area, the exact mechanisms of radiation cataractogenesis are still not fully understood. In particular, the question of the threshold dose for cataract development is not resolved. Cataracts have been classified as a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
174
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(183 citation statements)
references
References 37 publications
2
174
0
7
Order By: Relevance
“…[26][27][28] Workers like these butchers who work close to fire and heat sources are at high risk of developing crystalline lens clouding and some corneal diseases which can significantly impair their vision. While our studies found conditions limited to the anterior segment of the eye, other studies have reported posterior eye diseases related to working in environment similar to the cited abattoir.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Workers like these butchers who work close to fire and heat sources are at high risk of developing crystalline lens clouding and some corneal diseases which can significantly impair their vision. While our studies found conditions limited to the anterior segment of the eye, other studies have reported posterior eye diseases related to working in environment similar to the cited abattoir.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tissues of the central nervous system (CNS), lung, heart, liver, kidney, and gonads can be affected, whose turnover is slow [61,67]. The lens of the eye is also considered one of the most radiosensitive tissues in the human body and cataractogenesis can happen as a result [68]. Energy from radiation leads to the formation of excited and ionized molecules.…”
mentioning
confidence: 99%
“…Emami et al (2) estimated that there is a 5% and 50% risk of cataract formation at five years from 10 and 18 Gy considering dose incident on the lens of the eye. Alternate studies have proposed deterministic threshold doses of as low as 2 Gy acute doses and 4 Gy conventionally fractionated doses with further estimates that onset of cataract formation may occur after only 0.5 Gy suggesting a linear, no‐threshold complication model with a time to onset that is dose‐related 3 , 4 , 5 , 6 . As such, sparing of the lens during treatment is an important objective when preparing a patient's radiotherapy plan.…”
Section: Introductionmentioning
confidence: 99%